OP08 Long-term efficacy and pharmacodynamics of the anti-mucosal addressin cell adhesion molecule-1 (MAdCAM-1) monoclonal antibody SHP647 in Crohn's disease: the OPERA II study. (25th January 2019) - D'Haens, G; Reinisch, W; Lee, S D; Tarabar, D; Louis, E; Kłopocka, M; Klaus, J; Schreiber, S; Park, D I; Hébuterne, X; Gorelick, K J; Martin, S W; et al.
Abstract: Background: SHP647 is a fully human IgG2 anti-mucosal addressin cell adhesion molecule (MAdCAM-1) antibody in development for the treatment of Crohn's disease (CD). OPERA II, a multi-centre, open-label, Phase 2 extension study (NCT01298492), aimed to assess the long-term safety and efficacy of SHP647 in moderate-to-severe CD. Methods: Patients enrolled in OPERA II completed either 12 weeks' induction treatment (placebo or SHP647 22.5, 75, or 225 mg sc) in OPERA (NCT01276509) regardless of response, or had a clinical response (≥3-point Harvey–Bradshaw Index [HBI] score decrease) to SHP647 225 mg in TOSCA (NCT01387594). In OPERA II, patients received SHP647 (75 mg sc) every 4 weeks from Week 0–72 and were followed up monthly for safety for a further 24 weeks. Dose reduction to 22.5 mg owing to intolerance/adverse events or escalation to 225 mg owing to clinical deterioration/poor response was allowed from Week 8 as judged by the investigator. High-sensitivity C-reactive protein (hsCRP), faecal calprotectin (FC), and HBI score were assessed as exploratory efficacy endpoints. Results: Overall, 268 patients entered OPERA II and 149 completed; at baseline 169 patients from both OPERA and TOSCA were classed as responders (≥70-point decrease in Crohn's Disease Activity Index in OPERA or ≥3-point decrease in HBI in TOSCA) and 89 from OPERA were non-responders. Remission rate (HBI <5) initially decreased in responders and increased in non-responders from baseline to Week 8; it was then maintained in both groups to Week 72 (Figure 1a). No patients de-escalated dose, but 157 patients escalated to 225 mg. Those who escalated had slightly higher hsCRP and FC concentrations at baseline than those who remained on 75 mg (mean [95% CI] hsCRP, 22.8 [18.6, 27.0] vs. 20.5 [15.9, 25.1] μg/ml; mean [95% CI] FC, 2662.7 [1977.9, 3347.5] vs. 1988.8 [1501.0, 2476.7] mg/kg). Concentrations of hsCRP and FC decreased from baseline to Week 72 in both groups, but remained higher in those who escalated; the decline in hsCRP and FC was slower in those who escalated (Figure 1b and c). Mean changes over time in remission rates (Figure 1d) were similar in both groups after an initial decrease in those who remained on 75 mg and an initial increase in those who escalated. Conclusions: In this extension study, remission rates were sustained over 72 weeks with SHP647, regardless of initial response to induction treatment or dose-escalation status. hsCRP and FC levels were higher in patients who dose-escalated than those who remained on 75 mg. This adds to the evidence for long-term efficacy of SHP647.